PENGARUH EDUKASI TERHADAP PENGETAHUAN SISWA TENTANG HIV/AIDS DI TANGERANG TAHUN 2020 - Peni Surya Listyana; Meynur Rohmah (Nusantara Hasana Journal, 2021)
The prevalence of ODHA in the world in 2017 is 36.9 billion people, which has just freed 1.8 billion people. Of these there are 21.7 billion people living with HIV who have received antiretroviral treatment and including 940,000 people living with HIV (WHO, 2018). HIV / AIDS sufferers in Indonesia also experience an increase every year. A report from the Indonesian Ministry of Health in 2018 revealed that the number of reported cases of HIV cases was 301,959 people (47% of the estimated number of people living with HIV / AIDS or ODHA) in 2018 of 640,443 people, the condition in Indonesia was 75% infected with HIV from the age group adolescents (Pusdatin Kemenkes RI, 2018). Methods : Researchers used data bases such as google scholar, pubmed, researchgate to search for articles by authors searching Indonesian and English with the keywords "HIV AIDS education for students / HIV AIDS education for students" and "Knowledge of HIV / AIDS in students / Knowledge of HIV / AIDS in students ", to look for journal articles that cover vulnerable keywords within 5 years (2015-2020). Results : From 28 articles found that HIV / AIDS education carried out proved effective in increasing knowledge in students. Suggestion : This is made easier with technological advances, and therefore must be more careful in knowing that some information is received according to the truth.